Expression Profiles of the Ovine IL18 Gene and Association of Its Polymorphism With Hematologic Parameters in Hu Lambs - Zhang, Deyin; Zhang, Xiaoxue; Li, Fadi; Zhao, Yuan; Li, Xiaolong; Wang, Jianghui; Zhao, Liming; Yang, Xiaobin; Zhang, Yukun; Xu, Dan; Cheng, Jiangbo; Li, Wenxin; et al. (Frontiers in Veterinary Science, 2022)
Hematological traits are important indexes to evaluate health status and immunological conditions in human and livestock. In the current study, we measured the hematologic indexes of 819 male Hu lambs and performed the descriptive statistical analysis. The results showed the coefficients of variation of partial indexes were greater than 10%, and the heritability for five blood physiological indexes (MCV, WBC, HGB, HCT, and RDW_SD) were medium to high, ranging from 0.17 to 0.43. In addition, Interleukin 18 (IL18), as an important regulator of both innate and acquired immune responses, was selected as candidate gene and subjected to the expression profile analysis, single nucleotide polymorphism scanning and association analysis by using quantitative real-time PCR (qRT-PCR), PCR amplification, Sanger sequencing, and KASPar genotyping. The results of qRT-PCR indicated that IL18 is predominantly expressed in lymph and lung compared with that in the other tested tissues. In addition, three novel polymorphisms (g. 24991544 A > G, g. 24991651 A > G, and g. 24991749 C > T) were identified in IL18, and the three SNPs were in a strong linkage state. Therefore, only a SNP was genotyped and performed association analysis in the enlarged experimental population, the result of association analysis demonstrated that the polymorphism g. 24991651 A > G was significantly associated with RBC, MCV, MCHC and RDW_CV. These results will provide the reference values and the novel genetic markers of hematological parameters in sheep.